Gene therapy: Practical aspects of implementation. (6th May 2022) - Pipe, Steven W.; Reddy, K. Rajender; Chowdary, Pratima
Abstract: The first wave of gene therapies for haemophilia submitted for regulatory review utilize a liver‐directed approach in which a functional gene copy of factor VIII (FVIII) or factor IX (FIX) is packaged inside a recombinant adeno‐associated viral vector (rAAV). Following a single treatment event, these particles are taken up into liver cells, where the rAAV uncoats and delivers the DNA to the nucleus of the cell, where genetic elements that accompany the gene allow for efficient expression and secretion of FVIII or FIX protein into the plasma. An immune response to the vector capsid has been manifest by elevations in common liver enzymes that must be diligently followed postinfusion for weeks and months afterward and if signs of toxicity appear, will trigger a course of immunosuppression. Despite this, the studies have shown that this works in the great majority of individuals and the immunosuppression course is either avoided or short‐lived for many. Optimal outcomes in the haemophilia population will be dependent on proper screening assessment and maintenance of liver health prior to consideration of gene therapy, close short‐term follow up and implementation of immunomodulatory strategies to identify and manage liver toxicity and preserve durable transgene expression. This review proposes best practices to assist clinical teams with overcoming the challenges this platform of therapy poses to the traditional clinical care models and infrastructure within the haemophilia treatment centres (HTCs) who will be coordinating the patient's journey through this potentially transformative therapy. Abstract :